Performance of indirectly driven capsule implosions on NIF using adiabat-shaping. (May 2016) - Robey, H F; Smalyuk, V A; Milovich, J L; Döppner, T; Casey, D T; Baker, K L; Peterson, J L; Bachmann, B; Hopkins, L F Berzak; Bond, E; Caggiano, J A; Callahan, D A; et al.
Abstract: A series of indirectly driven capsule implosions has been performed on the National Ignition Facility to assess the relative contributions of ablation-front instability growth vs. fuel compression on implosion performance. Laser pulse shapes for both low and high-foot pulses were modified to vary ablation-front growth & fuel adiabat, separately and controllably. Two principal conclusions are drawn from this study: 1) It is shown that an increase in laser picket energy reduces ablation-front instability growth in low-foot implosions resulting in a substantial (3-10X) increase in neutron yield with no loss of fuel compression. 2.) It is shown that a decrease in laser trough power reduces the fuel adiabat in high-foot implosions results in a significant (36%) increase in fuel compression together with no reduction in neutron yield. These results taken collectively bridge the space between the higher compression low-foot results and the higher yield high-foot results.